PENGAKTUALISASIAN NILAI-NILAI PANCASILA DALAM KEHIDUPAN BERBANGSA DAN BERNEGARA OLEH MAHASISWA - Syalwa Poetrie Chiekal Amalia; Dinie Anggraeni Dewi (PENDIDIKAN SAINS DAN TEKNOLOGI, 2021)
Abstract: This research was made with the intention of knowing whether the students of SMKN 1 Bandung graduates have lived the life of the nation and state by actualizing them based on the values ​​in Pancasila. This research process was worked on using qualitative methods assisted by descriptive analysis, namely through a case study approach through respondents, namely students from SMKN 1 Bandung graduates. In addition, this research also uses literature review to add data sources from articles, journals, and books / ebooks. The results of this discussion are that there are still students who have not actualized the values ​​of Pancasila in the life of the nation and state. This could be due to a lack of understanding of Pancasila. Therefore, there is a solution to these problems, one of which is through learning Pancasila education. In Pancasila education, there are various kinds of knowledge that can develop and increase students' knowledge and understanding in carrying out the life of the nation and state. Because of its essence, Pancasila consists of five principles with different symbols, meanings and values. Therefore, students must motivate themselves so that they are enthusiastic in participating in Pancasila education learning. Students are agents of change, so they must be able to bring change to Indonesia and be able to maintain the unity of Pancasila as the main ideology of Indonesia.